The Monster's Transformation on American Radio (1930s–50s). - Barnes Echols, Katherine (University of Toronto Quarterly)
Radio listeners recognize a monster when they hear one, basing their imaginings on information they receive aurally. Vampires, werewolves, ghosts, aliens, and various creatures are adapted for radio from the pages of classic horror and science fiction tales written by Bram Stoker, Mary Shelley, Sheridan Le Fanu, Edgar Allan Poe, Robert Louis Stevenson, Guy de Maupassant, H.G. Wells, H.P. Lovecraft, and Ray Bradbury. Radio, an aural medium, relies on sound and description and, therefore, is ideal for horror. For the audience, listening to the radio is a subjective experience. The listener fills in the details and is free to conjure the monster in the imagination. This article explores the monster in a selection of American radio horror and science fiction programs that aired between the 1930s and 1950s and poses two questions: how does radio aurally render the monster for listeners and how does radio aurally convey horror?